Filipino silver market's functional and aesthetic needs in clothing - Manaloto, Mary Anne J.
ABSTRACT This study described the functional and aesthetic needs for top clothing of selected participants belonging to the silver market (those aged between 50 to 60 years old). This was a descriptive research that included a qualitative and quantitative approach. Through a focus group discussion and survey questionnaire, data was collected from sixty-four (64) respondents who were purposively selected for this study. The qualitative and quantitative analyses allowed the discovery of many findings and correlations such as gender playing an immense role in identifying the respondents top clothing preferences. This study also showed how the male and female respondents differ in clothing preferences, clothing priority and its manifestations, and perception of local retail brands. Top clothing needs were characterized as being functional and aesthetic. Functional and aesthetic top clothing needs have variables under each segment. The findings of the study included the Filipino silver market not being fully satisfied with local garment offerings despite perceiving local brands as providing top clothing needs. This study also showed how the respondent's occupation and the tropical weather affects their clothing preferences, therefore affecting their clothing priority and its manifestations. The result included how the male respondents tend to prioritize only the functional aspects of top clothing while the female respondents prioritize both functional and aesthetic top clothing needs. Apart from that, the findings of this study also included how the male respondents highly recommends the availability of fashion consultants in retail stores who can inform them what apparel style flatters them. To conclude, this study demonstrates the complex development and analysis in determining the clothing needs of a specific age bracket.